2024
DOI: 10.3748/wjg.v30.i9.1011
|View full text |Cite
|
Sign up to set email alerts
|

Impact of microplastics and nanoplastics on liver health: Current understanding and future research directions

Chun-Cheng Chiang,
Hsuan Yeh,
Ruei-Feng Shiu
et al.

Abstract: With continuous population and economic growth in the 21st century, plastic pollution is a major global issue. However, the health concern of microplastics/ nanoplastics (MPs/NPs) decomposed from plastic wastes has drawn public attention only in the recent decade. This article summarizes recent works dedicated to understanding the impact of MPs/NPs on the liver-the largest digestive organ, which is one of the primary routes that MPs/NPs enter human bodies. The interrelated mechanisms including oxidative stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 68 publications
(77 reference statements)
0
2
0
Order By: Relevance
“…Another major effect of MNPs on the digestive system is its impact liver function, studies have shown that MNPs can negatively impact liver function via oxidative stress and changes in cell function since the liver is the biggest digestive organ and a main gateway for MNPs to enter the body. MNPs have also been linked with clinical diseases such as metabolic dysfunction-associated fatty liver disease, steatohepatitis, liver fibrosis, and cirrhosis [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…Another major effect of MNPs on the digestive system is its impact liver function, studies have shown that MNPs can negatively impact liver function via oxidative stress and changes in cell function since the liver is the biggest digestive organ and a main gateway for MNPs to enter the body. MNPs have also been linked with clinical diseases such as metabolic dysfunction-associated fatty liver disease, steatohepatitis, liver fibrosis, and cirrhosis [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…Large pieces of PET plastics can be degraded into micro- or nanoscale fragments to form microplastics or nanoplastics following exposure to solar radiation, mechanical forces, or microorganisms . As previously reported, plastics, especially micro- and nanoplastics, are able to enter the human body. The accumulation of micro-/nanoplastics in organisms leads to adverse biological effects, thus posing a threat to organisms and human health. Previous studies have reported that the intake of PET plastics by living organisms triggers multiple biological and physiological defects, including inflammatory responses, reduced feeding activities, and energy depletion. However, the health risks and related toxicological mechanisms of PET plastics have yet to be comprehensively established, particularly the fate and metabolism of plastics in living organisms. To ascertain the fate of plastics in organisms, research on the degradation processes of plastics in vivo is required.…”
Section: Introductionmentioning
confidence: 95%